Proliferaton index in pituitary adenomas from a black African population (2016)
Background: The WHO has recognized a variant of pituitary adenomas with potential aggressive behavior which have been termed atypical pituitary adenomas. This group of tumours are recognized by their mitotic rate of more than >3%, p53 expression and invasion of surrounding structures. There has however been no study of the occurrence of these tumours in a black African population. This study is a preliminary attempt to examine this group of tumours in blacks. Methods: This study retrospectively reviewed fifty-seven histologically diagnosed and immunohistochemically characterized pituitary adenomas received in our department over a twenty-one year period. Specimens were stained with ki67, a nuclear marker of cell proliferation which has been identified as the single best predictor of atypical pituitary adenoma. Results: Twelve of the tumours showed atypical features with eight (67%) of these tumours being prolactinomas. Two of the tumours were gonadotrophs and two were null cell adenomas. There was no correlation with age or gender. Two of the tumours required neurosurgical re-exploration with one of these showing a higher mitotic index in the second biopsy. Conclusion: The study suggests similarity in the rate of occurrence of pituitary adenomas with atypical features in a black African population with what is seen in Caucasians. Prolactinomas constitute a significant percentage of the tumours with this feature